(untitled) (Archaeologia Adriatica, 2022)
Archaeological heritage of the island of Vis, including, for instance, Talež hillfort, ancient Issa or Vela Svitnja shipwreck, has a special meaning for many archaeologists drawn to the islands and the seas.